Effect of Pre-Tension and Orientation on the Springback Behavior of the Sheet Brass 65-35 - Abed, Aseel Hamad; Zaboon, Anwar Hassan (Al-Khwarizmi Engineering Journal, 2019)
One of the most important phenomenon that occurs in sheet metal forming processes is the spring-back, which causes several geometrical alterations in the parts. The accurate prediction of springback after bending unloading is the key to the tool design, operation control, and precision estimate concerning the part geometry. This study investigated experimentally the effect of pretension in three rolling direction (0, 90, 45 degree) on the springback behavior of the yellow brass, sheet under V shape bending die. The pre-tension ranges from five different levels starting of 11% to 55% from the total strain in each rolling direction by regular increase of 11 %, then bent on a V-die 90 degree for the springback estimate. From experiment the results revealat that the springback increment with increase pretension ratio and the springback in 45° rolling direction is considerable than the sbringback in 90° rolling direction and the springback in 90° is greater than the sbringback in 0° rolling direction.